2020
DOI: 10.1155/2020/9236234
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Long Noncoding RNAs lnc-DC in Plasma as a New Biomarker for Primary Sjögren’s Syndrome

Abstract: Objective. To evaluate the plasma levels of lnc-DC in primary Sjögren’s syndrome (pSS) patients and investigate the potential associations between lnc-DC and disease activity. Methods. In this study, we recruited 358 enrollments, including 127 pSS patients without immune thrombocytopenia (ITP), 22 pSS patients with ITP, 50 systemic lupus erythematosus (SLE) patients, and 50 patients with rheumatoid arthritis (RA) and 109 healthy individuals, from Xuzhou Central Hospital. The expression of anti-SSA and anti-SSB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Finally, in the study of Chen et al, plasma levels of lnc-DC, a dendritic cell-specific LncRNA, was also found upregulated in SS compared to healthy and disease controls including lupus and rheumatoid arthritis patients. An interesting finding was that longitudinally assessed samples revealed a decrease in Inc-DC plasma levels after treatment (22). Adding to the complexity of epigenetic modifications in SS, an emerging player has been recently proposed, the Circular RNAs.…”
Section: New Insights Into Ss Pathogenesis Genetics Epigenetics and E...mentioning
confidence: 97%
“…Finally, in the study of Chen et al, plasma levels of lnc-DC, a dendritic cell-specific LncRNA, was also found upregulated in SS compared to healthy and disease controls including lupus and rheumatoid arthritis patients. An interesting finding was that longitudinally assessed samples revealed a decrease in Inc-DC plasma levels after treatment (22). Adding to the complexity of epigenetic modifications in SS, an emerging player has been recently proposed, the Circular RNAs.…”
Section: New Insights Into Ss Pathogenesis Genetics Epigenetics and E...mentioning
confidence: 97%
“…Chen et al analyzed the lnc-DC level in the plasma of 127 pSS patients without ITP (immune thrombocytopenia), 22 pSS patients with ITP, 50 patients with SLE, 50 patients with RA, and 109 healthy individuals and reported that the lnc-DC level was significantly elevated in pSS patients, especially in pSS patients with ITP. The lnc-DC expression level was positively correlated with some clinical pSS characteristics, including the β 2 -microglobulin, anti-SSA and anti-SSB antibody levels, and the erythrocyte sedimentation rate [ 58 ]. The researchers suggested that through STAT3 regulation, lnc-DCs can induce Th17 cell differentiation and, therefore, the secretion of a variety of cytokines is involved in the occurrence and development of pSS [ 12 , 58 ].…”
Section: Autoimmune Disordersmentioning
confidence: 99%
“…The lnc-DC expression level was positively correlated with some clinical pSS characteristics, including the β 2 -microglobulin, anti-SSA and anti-SSB antibody levels, and the erythrocyte sedimentation rate [ 58 ]. The researchers suggested that through STAT3 regulation, lnc-DCs can induce Th17 cell differentiation and, therefore, the secretion of a variety of cytokines is involved in the occurrence and development of pSS [ 12 , 58 ]. Moreover, scientists found that the combined analysis of lnc-DC and anti-SSA/SSB antibody levels significantly improved the diagnostic ability and could be used to distinguish pSS patients from SLE and RA patients [ 58 ].…”
Section: Autoimmune Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…In pSS, IFN-α and their respective type I interferon-stimulated genes (ISG) contribute to distinct phenotypes, as several ISGs are associated with the presence of anti-SSA/ Ro or anti-SSB/La antibodies (10)(11)(12). Similarly, lncRNA expression profiles in labial salivary glands and plasma are increased in pSS patients compared to healthy donors (13,14). Consequently, it is plausible that different lncRNAmediated molecular mechanisms may be involved in the pathogenesis of pSS.…”
Section: Introductionmentioning
confidence: 99%